2006
DOI: 10.1111/j.1463-1326.2006.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte prolactin: regulation of release and putative functions

Abstract: Pituitary-derived prolactin (PRL) is a well-known regulator of the lactating mammary gland. However, the recent discovery that human adipose tissue produces PRL as well as expresses the PRL receptor (PRLR) highlights a previously unappreciated action of PRL as a cytokine involved in adipose tissue function. Biologically active PRL is secreted by all adipose tissue depots examined: breast, visceral and subcutaneous. The expression of adipose PRL is regulated by a non-pituitary, alternative superdistal promoter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
95
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 91 publications
(125 reference statements)
7
95
0
3
Order By: Relevance
“…In this study, both receptor isoforms were dramatically induced in epididymal preadipocytes during adipogenesis. A marked increase in total PRLR expression during adipocyte differentiation was also observed by others [14,15,16]. Regardless of the expression level of the PRLR, PRL further increased the expression of both isoforms (Fig 2).…”
Section: Discussionsupporting
confidence: 81%
“…In this study, both receptor isoforms were dramatically induced in epididymal preadipocytes during adipogenesis. A marked increase in total PRLR expression during adipocyte differentiation was also observed by others [14,15,16]. Regardless of the expression level of the PRLR, PRL further increased the expression of both isoforms (Fig 2).…”
Section: Discussionsupporting
confidence: 81%
“…Hyperprolactinemia adversely affects the fertility potential by impairing pulsatile secretion of GnRH and hence interfering with ovulation [10,13]. Recent studies have shown that prolactin may also be secreted from adipose tissue thus providing a link between obesity and hyperprolactinemia [14].…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that the increase of Pck1 activity for the Lobato studies was due to changes in adipocyte expression of Pck1 , because in our studies, we found prolactin increased Pck1 mRNA expression in isolated adipocytes from the mammary gland after prolactin administration. Prolactin has been shown not only to regulate lactation in the mammary gland, but also to regulate adipocyte metabolism ( 46 ). In WAT, Pck1 is increased during fasting to reesterify FA back to triglycerides after lipolysis.…”
Section: Discussionmentioning
confidence: 99%